1989
DOI: 10.1177/0011128789035003009
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Citizen Involvement in Policing

Abstract: People ask four things of police: to relieve fear and risk of crime, to manage disputes, to provide services, and to be accountable. Here the meeting of each of these objects is modeled as a subsystem of police/citizen interaction. Properly modeled, these four subsystems become isomorphic, or complementary. Taken together, the models provide a vision of how police and citizens can work together to give citizens greater control over their own disputes. While the vision may be quite different from current Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…But some of their comments indicate that time spent in the United States becomes a powerful factor that negatively (rather than positively) affects their views of authorities. Time in the United States has been found to affect a host of adjustment-related issues among immigrants (Lieberson 1980) and fear of crime rises and falls with time, as individuals feel more or less isolated in their communities (Pepinsky 1989). Cheurprakobkit and Bartsch (1999) found that Spanish-speaking Hispanics, in spite of language or cultural barriers, were more cooperative with the police and understood their work better than other groups, including Englishspeaking Hispanics.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…But some of their comments indicate that time spent in the United States becomes a powerful factor that negatively (rather than positively) affects their views of authorities. Time in the United States has been found to affect a host of adjustment-related issues among immigrants (Lieberson 1980) and fear of crime rises and falls with time, as individuals feel more or less isolated in their communities (Pepinsky 1989). Cheurprakobkit and Bartsch (1999) found that Spanish-speaking Hispanics, in spite of language or cultural barriers, were more cooperative with the police and understood their work better than other groups, including Englishspeaking Hispanics.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…It may rise or fall as a function of the degree of isolation people experience from one another (Pepinsky 1989;Warner and Rountree 1997); it can be affected by community composition (Moeller 1989) and by unexpected changes in the composition of a neighbourhood (Taylor and Covington 1993). Fear of crime can be linked to the social vulnerability of the person (Skogan and Maxfield 1981), race, ethnicity, or poverty (Moeller 1989;Madriz 1997aMadriz , 1997b.…”
Section: Perceptions Of Crime and The Criminal Justice Systemmentioning
confidence: 99%
“…This, in turn, might reduce their fear of crime. Along other lines, a field researcher might attempt to modify aspects of the neighborhood, e.g., improve street lighting, organize a Neighborhood Watch program, or increase the community involvement of police (Pepinsky, 1989). Measures of residents' activities after dark, both before and after such modifications, might provide behavioral evidence of less fear of crime.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in awareness and reports of crime that may come with, for example, neighborhood watch and other security precautions may in fact increase fear (Adams and Serpe 2000;Pepinsky 1989). Also, some claim that patrols from groups or organizations other than the police, such as security guards, police volunteers or other civilian groups, may be insufficient to satisfy public demands for more protection, because they do not have the same Bsymbolic aura^as the police (Loader 1997).…”
Section: Patrolling As a Methods To Increase Feelings Of Safety?mentioning
confidence: 99%